Pengembangan Aplikasi Manajemen Stok Berbasis RUP pada PT Anugerah Pelangi Nusantara - Siska Amelia; Migel Orvin Febryan; Novan Wijaya (MDP Student Conference, 2026)
A mobile-based inventory management application was developed for PT Anugerah Pelangi Nusantara to improve the accuracy and efficiency of stock management processes. The scope includes system analysis, design, implementation, and testing of an application that manages item data, stock-in and stock-out transactions, and inventory reports. The Rational Unified Process (RUP) methodology was applied through the inception, elaboration, construction, and transition phases. System modeling utilized Unified Modeling Language diagrams, while functional testing employed the black box testing method. The results indicate that the application successfully automates inventory recording, updates stock data in real time, and generates accurate inventory reports. All core system functions operated as expected during testing. Overall, the developed application reduces manual recording errors, accelerates reporting processes, and supports more efficient inventory control within the company.